(untitled) (Scientific journal of the Fergana State University, 2023)
The given article discusses the analysis of viyews on the linguistic field created in resent years in world linguistics, the interpretation of phenomena considered as a field, the relation of non-obstacle, studing in world linguistics, and the researches made by world scientists on the expression of this relation. Exact unobstructedness, approximate unobstructedness, and enhanced unobstructedness are explained in the researches of R.M. Teremova, and the researches of O.A. Lavrova, V.Y. Apresyan, G.A. Musatova are also referred to. In the work, the works of the above-mentioned scientists were analyzed, the meaning of non-obstacles was given in scientific works, and opinions about non-obstacles were summarized.